The Impact of Memorable Culinary Tourism Experience, Local Food Enjoyment and Food Safety on Revisit Intention Mediated by Tourist Satisfaction (A Study on Nasi Kapau Visitors in Bukittinggi City) - Setyawan, Caren; Verinita, Verinita; Syafrizal, Syafrizal (Dinasti Review, 2025)
This study aims to examine the impact of Memorable Culinary Tourism Experience (MCTE), Local Food Enjoyment, and Food Safety on revisit intention, mediated by tourist satisfaction, among Nasi Kapau visitors in Bukittinggi City. A quantitative approach was employed, with purposive sampling of 225 respondents who had visited and tasted Nasi Kapau at least twice. Data collection was conducted using online questionnaires distributed via WhatsApp and Instagram, and the analysis was performed using SmartPLS 4.0. The results indicate that, MCTE has a positive and significant effect on revisit intention. Local Food Enjoyment has a positive and significant effect on revisit intention. Food Safety has a positive but insignificant effect on revisit intention. MCTE has a positive and significant effect on tourist satisfaction. Local Food Enjoyment has a positive but insignificant effect on tourist satisfaction. Food Safety has a positive but insignificant effect on tourist satisfaction. Tourist satisfaction has a positive and significant effect on revisit intention. Tourist satisfaction positively and significantly mediates the relationship between MCTE and revisit intention. Tourist satisfaction positively but insignificantly mediates the relationship between Local Food Enjoyment and revisit intention. Tourist satisfaction positively but insignificantly mediates the relationship between Food Safety and revisit intention. These findings emphasize the importance of enhancing memorable culinary experiences and local food enjoyment to increase tourist satisfaction and revisit intention in Bukittinggi City's culinary tourism.